The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/lno.10671
|View full text |Cite
|
Sign up to set email alerts
|

Coping with waves: Plasticity in tidal marsh plants as self‐adapting coastal ecosystem engineers

Abstract: Tidal marsh vegetation is increasingly valued for its role in ecosystem‐based coastal protection due to its wave dissipating capacity. As the efficiency of wave dissipation is known to depend on specific vegetation properties, we quantified how these morphological, biochemical, and biomechanical properties of tidal marsh vegetation are, in turn, affected by wave exposure. This was achieved by field measurements at two locations, with contrasting wave exposure, in the brackish part of the Scheldt Estuary (SW Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 51 publications
10
69
1
Order By: Relevance
“…The wave and flow attenuation rates that are reported in the literature, and that were typically measured during summer peak‐biomass conditions (Leonard and Croft ; Ysebaert et al ; Silinski et al ), are in the same range as our measurements for summer peak biomass. However in the present study, wave and flow attenuation rates were measured throughout the season.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The wave and flow attenuation rates that are reported in the literature, and that were typically measured during summer peak‐biomass conditions (Leonard and Croft ; Ysebaert et al ; Silinski et al ), are in the same range as our measurements for summer peak biomass. However in the present study, wave and flow attenuation rates were measured throughout the season.…”
Section: Discussionsupporting
confidence: 80%
“…Tidal pioneer marshes in the temperate climate regions may lose much of their aboveground biomass in winter which temporarily reduces the efficiency of the marsh for shoreline protection. Although the general processes of wave attenuation (Ysebaert et al ; Yang et al ; Möller et al ; Silinski et al ) and erosion reduction (Chen et al ; Francalanci et al ; Wang et al ) by tidal marshes are well studied, studies are mostly done under peak‐biomass (summer) conditions while studies under low biomass (winter) conditions are sparse (Coulombier et al ; Spencer et al ; Vuik et al ). In this study, we quantify seasonal changes in wave attenuation rates and sedimentation‐erosion rates in pioneer marsh vegetation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field data for flexural rigidity show an order of magnitude of variation in values. Previous studies of both freshwater and saltwater vegetation have also demonstrated large intraspecific variation in values for flexural rigidity between samples on different stems from the same site (Feagin et al, 2011;Miler et al, 2012;Paul et al, 2014;Rupprecht et al, 2015), and it is also likely that flexural rigidity varies depending on patch exposure to the flow and the local age of vegetation patches (Anderson & Smith, 2014;Silinski et al, 2018). The simplified model results (Figure 13c) demonstrate that the range of predicted flexural rigidities agrees well with the observed range.…”
Section: Journal Of Geophysical Research: Earth Surfacementioning
confidence: 99%
“…For high waves (significant wave heights over 1 m), relatively tall plant species will lose the majority of their aboveground biomass; a large-scale flume experiment showed 80% stem breakage of Elymus athericus (Rupprecht et al, 2017), and 50% reduction in stem density of Spartina alterniflora was observed after a Category 1 hurricane (Gittman et al, 2014). Plants at locations exposed to higher mean wave energy develop shorter and thicker stems, which makes them less vulnerable to stem breakage (Silinski et al, 2018). This implies that, similar to morphological stability, locations with low mean wave energy are most sensitive to stem breakage during severe episodic storm events (Fig.…”
Section: Stability Of Salt Marshes During Stormsmentioning
confidence: 99%